Критична мовознавча спадщина на сторінках журналів Червоний шлях (1923–1936) та Життя й революція (1925–1934) - Julia Rysicz-Szafraniec (Acta Universitatis Wratislaviensis. Slavica Wratislaviensia)
The article is devoted to the study of linguistic texts, namely reviews, published in two Ukrainian journals which played an active role in the field of scientific journalism in the 1920s and 1930s. This study was conducted according to the principles of descriptive analysis. The structure of selected reviews is presented, as well as an outline of certain issues that were unresolved in the contemporaneous study of language, such as the question about the origin of the Ukrainian language or the issues of language norm or description of phonetic phenomena. In addition, the issue of two linguistic schools in Ukraine of that period was raised and their confrontation was outlined based on the analyzed texts.